2010
DOI: 10.1097/inf.0b013e3181b20e93
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Routine Hepatitis B Immunization on the Prevalence of Chronic Hepatitis B Virus Infection in the Marshall Islands and the Federated States of Micronesia

Abstract: Hepatitis B vaccination has resulted in a substantial decline in chronic infection in children in the Pacific Islands. HB vaccine effectiveness is high in this region, despite challenges in providing HB vaccine at birth and completing vaccination series on schedule.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 17 publications
0
24
0
1
Order By: Relevance
“…They found birth dose vaccination was 48% in Chuuk, 87% in Pohnpei (both Micronesia) and 49% in the Marshall Islands. 33 Complete vaccination (three doses) was 87% in Chuuk, 90% in Pohnpei, and 93% in the Marshall Islands. 33 HBsAg prevalence among children in the region was 2.5% in Chuuk, 1.5% in Pohnpei, and 1.8% in Marshall Islands.…”
Section: Hbv Prevention Strategies In Pictmentioning
confidence: 99%
“…They found birth dose vaccination was 48% in Chuuk, 87% in Pohnpei (both Micronesia) and 49% in the Marshall Islands. 33 Complete vaccination (three doses) was 87% in Chuuk, 90% in Pohnpei, and 93% in the Marshall Islands. 33 HBsAg prevalence among children in the region was 2.5% in Chuuk, 1.5% in Pohnpei, and 1.8% in Marshall Islands.…”
Section: Hbv Prevention Strategies In Pictmentioning
confidence: 99%
“…In one paper, authors indicated that poor quality IIS data could not be used to calculate immunization history, therefore mean vaccine coverage statistics were used to determine the denominators for VE calculations, rather than using IIS data directly [36]. Another study used IIS data to generate vaccination rates for the population, but applied these rates to mean disease levels to conclude that implementation of vaccination had decreased incidence of disease [37].…”
Section: Discussionmentioning
confidence: 99%
“…Study results were reported as changes in rates of incident disease as a result of implementation of vaccination or another intervention. Studies were retrospective if authors assessed or evaluated a vaccine program following its implementation [6,[36][37][38][39][40]. One paper prospectively monitored the impact of a vaccine intervention at the beginning of program implementation [8].…”
Section: Use Of Registry Data In Ve Studiesmentioning
confidence: 99%
“…(11)(12)(13)(14)(15)(16)(17) The limited data that is available shows that the Marshallese face significant health disparities with higher rates of obesity, diabetes, cardiovascular disease, and infectious diseases than the US population. (18)(19)(20)(21)(22)(23) Additionally, Marshallese living in Arkansas face challenges with social determinants of health including low-income employment, low educational attainment, limited English proficiency, and multiple barriers to healthcare access. (24)(25)(26) In 2007, the University of Arkansas for Medical Sciences (UAMS) established a regional campus in northwest Arkansas with 3 rd and 4 th year medical and pharmacy students, as well as graduate programs in nursing and physical therapy.…”
Section: Introductionmentioning
confidence: 99%